Learning Media Development of Augmented Reality Hair Coloring - Tritanti, Asi; Juniastuti, Eni; Pranita, Ika; Agrevinna, Mausa; Kamis, Arasinah (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study addresses the challenges of conventional teaching methods in cosmetology education by developing a mobile Augmented Reality (AR) application for hair coloring. The primary objective is to enhance students' learning experiences and achievements through interactive AR content. Using the ADDIE model, we created an Android-based AR system that integrates Vuforia Engine for marker-based tracking and ARCore Face API for facial recognition. The methodology involved a descriptive analytical approach with expert validation to assess usability and content accuracy, followed by user testing with final-year students. The findings reveal that while the AR application has potential, it faces technical challenges, including prolonged download times and device compatibility issues. The implications of this research highlight the need for improvements in user interface design, system stability, and content accuracy to optimize the learning experience. By addressing these issues, the study aims to contribute to the effective integration of digital technologies in vocational education, ultimately preparing students for success in the beauty industry.